Ten years after 9/11 rethinking the jihadist threat - Acharya, Arabinda (Routledge security in Asia Pacific series, 2013)
Ten years after the 9/11 attacks, this book reassesses the effectiveness of the "War on Terror", considers how al-Qaeda and other jihadist movements are faring, explores the impact of wider developments in the Islamic world such as the Arab Spring, and discusses whether all this suggests that a new approach to containing international, especially jihadist, terrorism is needed